THE INFLUENCE OF TOTAL MEMBERS, OWN CAPITAL AND BUSINESS VOLUME SAVED AND LOAN ON THE REMAINING OF BUSINESS RESULTS (Empirical Study on Indonesian Employee Cooperatives In Bangkinang and Kuok 2010-2019 years) - Fegi Amalia; Syamsul Bahri; Irfan Tanjung (STIE Bangkinang Publishing, 2021)
This research was conducted with the aim of examining the effect of the number of members, own capital and the volume of savings and loan businesses on the remaining business results of the employee cooperatives of the Republic of Indonesia in Bangkinang Kota and Kuok districts in 2010-2019. The population in this study were all employee cooperatives of the republic of Indonesia in Bangkinang sub-district and Kuok sub-district in 2010-2019, as many as 24 cooperatives. The technique used in sampling is purposive sampling method, the sample in this study was selected as many as 4 cooperatives. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 23.00 for windows. The results showed that simultaneously the number of members, own capital and the volume of savings and loan businesses had a joint effect on the residual income. Partially the variables of own capital and business volume had an effect on the residual income while the variable number of members had no effect on the residual results of the business. The closeness of the relationship between the independent variables and the dependent variable is classified as strong. The contribution of the independent variable to the dependent variation is 55.8%.